Pengaruh Ekspor, Impor, dan Nilai Tukar terhadap Pertumbuhan Ekonomi di Indonesia Periode 2014-2023 - Safira Amanda Novianingrum; Sellya Nara Kartika; Uswatun Khasanah; Muhammad Kurniawan (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
The purpose of this study was to determine the effect of exports, imports and exchange rates on economic growth in Indonesia in 2014-2023. The method used in this research is quantitative using secondary data in the period 2014-2023. The data in this study were obtained from literature studies, namely financial statistics of district and city governments 2014-2023. This study uses multiple linear regression analysis methods and uses several classical assumption tests. To process data using several tests, namely Statistical Test and Classical Assumption Test. The data is processed using the Eviews-13 application. The results of this study indicate that exports had a negative and insignificant effect on economic growth in Indonesia in 2014-2023, imports had a positive and insignificant effect on economic growth in Indonesia in 2014-2023 and the exchange rate had a negative and insignificant effect on economic growth in Indonesia in 2014-2023. Based on the analysis using the Eviews-13 tool, it is obtained that exports, imports, and exchange rates affect economic growth in Indonesia by 42% while the remaining 58% is influenced by other variables not included in this study.